THE ENVIRONMENTAL AND ECONOMIC IMPACTS OF GREEN PRODUCTS IN THE FOOD INDUSTRY - AN ANALYTICAL STUDY IN IRAQ - Muthana Khuder Irhayyam (Scholars Digest Publishing, 2025)
This research examined green production adoption in Iraq's food industry, analyzing drivers, carbon footprint effects, and consumer behavior. Using quantitative methods with 228 survey responses and SPSS analysis, it found green products reduce 53% of emissions, while economic barriers showed limited impact. Results indicated consumer eco-awareness drives sustainable purchases, though policy implementation gaps persist. Recommendations include integrated financing, monitoring, and awareness programs to strengthen green transition. The study followed rigorous academic methodologies with verified data sources.
Keywords: Green products, Environmental awareness, Economic challenges, Government policy, Carbon footprint, Purchasing decisions, Shift towards green production, Food industries.